Design of Molecular Diversity by Olefin Metathesis in Tandem with Other Reactions - Kotha, Sambasivarao; Gupta, Naveen Kumar; Ansari, Saima; Singh, Deepshikha (Synlett, 2024)
This review summarizes various strategies that combine metathesis with diverse named and unnamed reactions to create molecular diversity in producing carbocycles, macrocycles, and heterocycles.1 Introduction2 Olefinations3 Rearrangement4 Allylation5 Cycloadditions6 Coupling Reactions7 Grignard Reaction8 Radical reactions9 Conjugate Addition–Metathesis10 Multicomponent Reactions11 Miscellaneous12 Conclusions
Keywords: metathesis; molecular diversity; carbocycles; macrocycles; heterocyclic compounds